From Symbolic Representation to 2D Spatial Manipulation: A Transcription of Fractal Models from OpenMusic to Max - Bonduki, Said; Rossetti, Danilo; Simurra, Ivan (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação Musical, 2025)
This article presents a project focused on the transcription of patches for musical composition and analysis originally developed in the OpenMusic environment into Max/MSP, with particular emphasis on the implementation of a compositional model based on fractals proposed by Mikhail Malt. The model employs Iterated Function Systems (IFS) to generate fractal structures that control frequency and temporal parameters in music, initially applied in the composition Six Fractal Contemplations. The transcription aims to explore the capabilities of Max/MSP to integrate symbolic notation (through the Bach library) and graphical visualization (via the CNMAT library), thereby enhancing the accessibility and expanding the functionalities of historically significant tools in Computer-Assisted Composition (CAC). It is concluded that the model offers a bridge between mathematical abstractions and creative processes, reinforcing the relevance of CAC in both preserving and innovating computational tools for music.